INTEGRASI SISTEM OTENTIKASI KEAMANAN NIRKABEL BERBASIS WPA/WPA2 ENTERPRISE DAN CAPTIVE PORTAL MENGGUNAKAN PROXY RADIUS STUDI KASUS: STANDAR JARINGAN NIRKABEL UNIVERSITAS GADJAH MADA - , Josua M. Sinambela; , Ir. Lukito Edi Nugroho, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Convenience and mobility in wireless networks become an attraction for computer users who use this technology to access a computer network or the Internet. Problems are often encountered when implementing a wireless network is security-related issues, one of them is the authentication or how to ensure the user has access to a wireless network and how to monitor the use of the network. Gadjah Mada University consists of many department, each deparment has a wireless network infrastructure by way of infrastructure management is quite diverse. Security system which is applied in general is still diverse, some systems already use a wireless network authentication security system based on captive portal, which connect to the database accounts in the department. Many units are working to apply the authentication system with just activate the WEP or WPA encryption that uses key / passphrase authentication specified as the key to connect with wireless network. Administration and management of user accounts and key or passphrase not effective because it raises many new issues such as key or passphrase is easy to share or if captive-portal accounts are only used for wireless access cause the user does not maintain his account. This research produced a solution that is a security system authentication integration on a wireless network at Gadjah Mada University which will become a wireless network management standard. This system will allow the accounts within a specific work unit or department can be used on other work units or department, so no longer needed the registration of different units, either by using an account on the unit itself or accounts at the central account. The study also regulate how the use of authentication systems at the central level provided by the Center for Information and Communication Technology Services (PPTIK) UGM. This research recommends the implementation of authentication system based on WPA/WPA2 Enterprise and Captive Portal using a Radius Server and Radius Proxy that can be integrated account management and simplify wireless network user administration within the Gadjah Mada University